1927 Ind. Acts 469, § 1 - (:unkn) unknown (My University, 1927)
Public Offenses - Ownership, Possession or Control of Machine Guns or Bombs - Penalty, ch. 156, § 1: Prohibited owning or possessing a machine gun or bomb in an automobile. Punishable by imprisonment for 1-5 years.
Keywords: MACHINE GUN RESTRICTION